2018
DOI: 10.1021/acs.biochem.8b01097
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-Dependent Formation of Nuclear Granules Containing FUS and RNA Pol II

Abstract: Purified recombinant FUsed in Sarcoma (FUS) assembles into an oligomeric state in an RNA-dependent manner to form large condensates. FUS condensates bind and concentrate the C-terminal domain of RNA polymerase II (RNA Pol II). We asked whether a granule in cells contained FUS and RNA Pol II as suggested by the binding of FUS condensates to the polymerase. We developed cross-linking protocols to recover protein particles containing FUS from cells and separated them by size exclusion chromatography. We found a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 72 publications
3
57
0
Order By: Relevance
“…Indeed, it was previously reported that the N-terminus of FUS is required for binding of FUS to chromatin (Yang et al, 2014), where FUS localises to granules and regulates gene expression in a transcription-dependent manner. Moreover, inhibition of transcription leads to cytoplasmic relocalisation of FUS, suggesting that active transcription tethers FUS to newly synthesized RNA bound to chromatin (Patel et al, 2015;Thompson et al, 2018;Zinszner et al, 1994). This is consistent with the recent finding that FUS leaves the nucleus through passive diffusion .…”
Section: Llps Is Required For the Association Of Fus With Chromatin Asupporting
confidence: 91%
See 4 more Smart Citations
“…Indeed, it was previously reported that the N-terminus of FUS is required for binding of FUS to chromatin (Yang et al, 2014), where FUS localises to granules and regulates gene expression in a transcription-dependent manner. Moreover, inhibition of transcription leads to cytoplasmic relocalisation of FUS, suggesting that active transcription tethers FUS to newly synthesized RNA bound to chromatin (Patel et al, 2015;Thompson et al, 2018;Zinszner et al, 1994). This is consistent with the recent finding that FUS leaves the nucleus through passive diffusion .…”
Section: Llps Is Required For the Association Of Fus With Chromatin Asupporting
confidence: 91%
“…Importantly, several proteins enriched with phase separated FUS, such as DDX3X, DHX9, FMR1, TIAR-1 and SMN1 (compare Supplementary Table 1), have already been observed by others to co-localize with FUS into cytoplasmic granules (Blokhuis et al, 2016;Bosco et al, 2010;Groen et al, 2013;Kamelgarn et al, 2016). Moreover, proteins found in nuclear granules, specifically paraspeckles (Shelkovnikova et al, 2014) and transcription-dependent granules containing FUS and RNA Pol II (Thompson et al, 2018) are highly enriched under LLPS conditions compared to non-LLPS conditions (compare data in Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations